Plantation of Trees and Shrubs in Carbon Polluted Areas Could Reduce Carbon Dioxide from the Atmosphere - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez (International Journal of Bio-resource and Stress Management, 2023)
The increasing global warming associated with the constant emission of carbon dioxide by combustion of fossil fuels from the factories and burning of woods poses a great menace in increasing pollution in the atmosphere; thereby, endangering the security of mankind and animals. Besides, this increased global warming is associated with incessant logging, illegal anthropogenic activities and conversion of forest to agriculture. The constant emission of greenhouse gases (GS), in particular the CO2 load in the atmosphere have increased several folds leading to pollution and climate change. This has direct impact on climate changes in enhancing and increased global warming. This has caused a great concern to the security of mankind and animal life, thereby leading to reduced crop productivity Worldwide. Concerted research activities have been directed worldwide to mitigate it. Plants capture carbon and store it in various reserves. Different technologies are being adopted in different countries for CO2 capture and sequestration but attained little success to reduce CO2 load from the atmosphere.